PENGARUH LIMITASI NUTRIEN PADA FERMENTASI ASAM SITRAT BIAK-RENDAM,SECARA 2-TAHAP DENGAN Aspergillus niger ATCC 11414 - Milono Poesponegoro; Oei Ban Liang (Research Center for Chemistry - LIPI, 1991)
The aim of the study was to determine the type and level of nutrient limitation for stimulation of citric accumulation by Aspergillus niger ATCC 11414. The study focused all the effects of substrate concentration, nutrient limitation and the concentration of pre-cultred mycelium on citric acid accumulation. Citric acid fermentailon was carried out by a 2-stage process, where the growth stage and citric acid production stage were done separately, either using shake-flask culture or stirred fermentcr method. The fermentation process was followed by monitoring the changes in the pH value and in the concentrations of total reducing sugars, cellular biomass, and citric acid in the culture medium. Results of the study showed that nutrient limitation inhibited the growth of mould and could be all important factor for stimulation of citric acid accumulation by Aspergillus niger ATCC 11414. Phosphorous limitation was found to be the most effective than the limitation of other nutrients tested, for stimulation of citric acid accumulation. The results also revealed that there was a relationship between phosphorous limitation, mycelium concentration and the efficiency of citric acid production by Aspergillus niger ATCC 11414.